Assessing decision-making skills with the Script Concordance Test (SCT) in clinical neurology and emergency medicine - Helena-Fee Gudorf; Maximilian Heidrich; Kristoph Rauchstädt; Raphael Scherbaum; Lars Tönges; Anne-Sophie Biesalski (BMC Medical Education)
Abstract Background Clinical reasoning is an essential medical competence that should be taught and assessed from the beginning of medical studies. These skills can be evaluated using the Script Concordance Test (SCT), which presents daily clinical scenarios characterised by uncertainty. Due to the lack of validated research on this method in Germany, particularly in the field of neurology, we developed and implemented an SCT at Ruhr University Bochum. We compared different teaching methods (clinical seminar vs. digital video course) and their outcomes on the examination. Methods A group of 6th-year medical students who had received the same education completed an SCT after participating in either a clinical seminar or a digital video course. The SCT was developed using blueprints on stroke and epilepsy. The test consisted of 40 case vignettes with a total of 120 items. Initially, experts completed the test to establish the reference panel. The final high-stakes examination was created using the aggregate scoring method and an item analysis. Results The SCT was completed by 15 experts and 59 students. The final SCT consisted of 112 items and achieved a Cronbach’s alpha of 0.85. A significant difference (p < 0.05) was observed between the experts, who achieved a mean score of 81.75, and the students on the first assessment day, who achieved a mean score of 68.92. No significant differences were found between the groups (interactive video course and seminar) or assessment time points. The questionnaire revealed a sense of insecurity in clinical decision-making before the SCT and highlighted the need to incorporate clinical reasoning practices from the beginning of medical studies to mitigate fear in uncertain situations. The SCT helped students structure decision-making processes and and improved their confidence in making decisions. Conclusion The SCT is a reliable and valid tool for assessing medical students throughout their university education. Regular exposure to the SCT format would facilitate familiarity with its structure. We propose utilising the SCT as a learning tool rather than solely for assessment purposes. For instance, it could be integrated into teaching methodologies as a think-aloud exercise or incorporated into progress tests.